SEDUHAN BUNGA ROSELLA TERHADAP TEKANAN DARAH PADA HIPERTENSI - Rina Budi Kristiani; Sosilo Yobel (Bahasa Indonesia, 2022)
Hypertension is an increase in blood pressure > 140/90 mmHg is the result obtained with two measurements. Hypertension can be prevented and controlled with non-medical and medical treatment, non-medical treatment including maintaining weight, regulating diet, avoiding alcoholic beverages and cigarettes and steeping rosella flowers. This study aims to see the difference in blood pressure in the control and intervention groups after giving Rosella flower water steeping. The method used is a quasi-experimental pre-post test with a control group of 36 respondents, using a purposive sampling technique to determine the sample, with the intervention group (given rosella flower steeping) totaling 18 respondents and the control group totaling 18 respondents. The data obtained were carried out by the Wilcoxon and Mann Whitney U statistical tests. Data analysis using the Wilcoxon statistical tests in the intervention and control groups showed sig 2 tailed = 0.000 and 0.248 and the Mann Whitney U statistical test showed 0.000 meaning that there was a difference in blood pressure in the control and intervention group respondents. after giving rosella flower steeping. Steeping rosella flowers can be used as an alternative non-drug therapy to control blood pressure in patients with hypertension. Keywords: Rosella Flower Stew, Blood Pressure, Hypertension